Verhaltensforschung am Point of Sale Ansatzpunkte und Methodik - Silberer, Günter (Universitätsverlag Göttingen, 2009)
Many buying decisions are made at the Point of Sale. This fact underlines the outstanding importance of behaviourism, its methods and its efficiency. Therefore this work deals with the classical as well as with recent research methods into buying habits, etc. Validity aspects receive special attention. To demonstrate how much information can be gathered with relatively little effort an adapted form of research at the POS is described. Also suggestions are given to look into the behaviour of the staff at the POS.